Postoperative surveillance using low-dose computed tomography for non-small-cell lung cancer. (28th November 2022) - Nakada, Takeo; Takahashi, Yusuke; Sakakura, Noriaki; Masago, Katsuhiro; Iwata, Hiroshi; Ohtsuka, Takashi; Kuroda, Hiroaki
Abstract: OBJECTIVES: We retrospectively analysed the surgical prognosis of patients with pathological stage I non-small-cell lung cancer (NSCLC) who after complete resection underwent low-dose computed tomography (LDCT) or conventional CT as postoperative surveillance. METHODS: We investigated 416 patients who underwent lobectomy or segmentectomy between January 2013 and December 2016. We compared the prognosis between the LDCT and conventional CT groups using the propensity score-matched analysis. RESULTS: The median follow-up period was 57 months. Cancer recurrence occurred in 47 patients (11.3%). In the entire cohort ( n  = 416), recurrence-free survival (RFS) and overall survival (OS) were better in the LDCT group ( P  = 0.001 and 0.002, respectively). Both intrathoracic recurrence and distant metastasis were higher in the conventional group ( P  = 0.015 and 0.009, respectively). However, there was no statistical difference in the factors leading to recurrence detection (routine radiological examination, symptoms and elevated tumour markers: all P  > 0.05). Both groups were matched using a ratio of 1:1. The area under the receiver operating characteristic curve was 0.788. A total of 226 patients were successfully matched. After matching, there was no statistical difference between the 2 groups for RFS and OS ( P  = 0.263 and 0.226). There were also no statistical differences in recurrence rate, the factors leading to recurrence detection or recurrence site (all P  > 0.05). CONCLUSIONS: After using propensity score matched, RFS and OS did not differ significantly between LDCT and conventional CT groups. Retrospective comparisons suggest no disadvantages of using LDCT for postoperative surveillance of pathological stage I NSCLC. Further validation will be needed in the future. Abstract : Lung cancer is the most common cancer worldwide with an increasing mortality rate.